2018
DOI: 10.1177/0961203318808589
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of sequential 13-valent conjugated and 23-valent unconjugated pneumococcal vaccines in a population of children with lupus

Abstract: Pneumococcal vaccination is recommended as a quality indicator for management of children with systemic lupus erythematosus. Literature on the immunogenicity of pneumococcal vaccines (PCVs) in children is scant. We sought to prospectively evaluate via an observational study, the immunogenicity to sequential children with lupus. Out of a cohort of 26 patients, approximately 65% achieved > 70% vaccinated serotype antibody levels of > 1.3 mcg/dL following PCV13, and of 22 patients followed through PPSV23 vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…155 This is further supported by a recent study showing decreased efficacy of influenza vaccination in patients treated with adalimumab but not ustekinumab. 156 In patients exposed to rituximab, most studies found a reduced humoral response to pneumococcal, 101,112,115,[126][127][128]135,157 hepatitis B, 136 and influenza vaccination. 73,108,111,116,122,130,142,144 Rituximab exposure did not significantly affect humoral response to seasonal influenza vaccination in patients with autoimmune blistering disease.…”
Section: Vaccines and Biologicsmentioning
confidence: 99%
“…155 This is further supported by a recent study showing decreased efficacy of influenza vaccination in patients treated with adalimumab but not ustekinumab. 156 In patients exposed to rituximab, most studies found a reduced humoral response to pneumococcal, 101,112,115,[126][127][128]135,157 hepatitis B, 136 and influenza vaccination. 73,108,111,116,122,130,142,144 Rituximab exposure did not significantly affect humoral response to seasonal influenza vaccination in patients with autoimmune blistering disease.…”
Section: Vaccines and Biologicsmentioning
confidence: 99%
“…19,20 Studies have revealed that vaccines are generally safe in this patient population and do not result in a disease flare. 10,13,14,21,22 Except for live vaccines, which are contraindicated in patients receiving immunosuppression, recommended inactivated childhood vaccines should be administered to patients with c-SLE. 15 In this quality improvement (QI) study, we evaluated our baseline compliance with pneumococcal vaccination recommendations in patients with c-SLE and identified barriers to vaccination and opportunities to increase pneumococcal vaccination in the rheumatology clinic through multiple plan-do-study-act cycles.…”
mentioning
confidence: 99%
“…An increase in antibodies was also seen after immunization with PPV23 except for one serotype, but the increase was not significant. Although the evaluation of the vaccine response was performed differently, this is in line with recent studies of paediatric lupus patients 11 and adults with rheumatoid arthritis. 20 Both studies showed a response to pneumococcal immunization but also a higher response after PCV13 than PPV23.…”
Section: Discussionmentioning
confidence: 65%
“…10 The knowledge about response to pneumococcal immunization in children with rheumatic disease and compromised immune system is sparse. Previous studies of children with systemic lupus 11 and JIA 12,13 have shown a response to immunization although it may be dampened in patients treated with TNF-alpha inhibitors. 12 It is difficult to compare the serologic response to pneumococcal immunization between studies due to different vaccine regimens and definitions of response.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation